Ethnomedicines Medicinal Plant In Pujon District, Malang Regency, East Java - Tika Putri Agustina (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Traditional medicine is currently being abandoned by the community because its use is considered impractical and when it is taken in the form of medicine it tastes bad. Traditional medicine usually uses medicinal plants obtained from the surrounding environment. The community grows plants that are useful for daily life near the house, such as in the yard. Traditional medicine is one of the fastest ways to obtain the latest medicinal sources from plants that have been used by the community for generations. For this reason, research on ethnomedicine needs to be carried out. The people in Pujon District still practice traditional medicine to cure several diseases. A total of 47 species of plants in the garden are used as medicinal plants